(untitled) (Foro de Educacion, 2025)
Scientific argumentation is an essential feature of science learning because it prepares students to make arguments based on evidence that helps them to argue critically. This article was based on a study that sought to ascertain the implications of incorporating socio-scientific issues (SSI), organised peer discussion tasks and explicit instruction on critical thinking of scientific argumentation of upper primary school in China. A questionnaire survey was used, and a quantitative cross-sectional research design was carried out, where 100 students were surveyed. The results revealed that all three strategies used strongly predicted the ability of argumentation, with the most significant effect coming in the SSI integration and then closely followed by the structured peer discussion and explicit instruction. This research study reveals that the combined model is the best way of encouraging scientific argumentation. It suggests the combination of SSI and organised discussions and a famous bone-up instruction. In practice, this can lend itself to lesson planning so that content and reasoning skills are considered equal. Limitations: One is the absence of causality, two is non-self-reporting, and three is an inadequate sample size.